Educação intercultural: a visao dos agentes educacionais sobre as vivências dos alunos sateré-mawé nas escolas municipais de Parintins - Oliveira, Beatriz da Silva de (Brasil, 2023)
The school must be a democratic space, which under the light of constitutional principles and legislation must ensure access to education for all, without making social, cultural and ethnic distinctions. In this way, this study has as main objective to know the experiences of the students of the Sateré-Mawé ethnic group in the urban schools of the municipal network of Parintins-AM. To reach it successfully, the methodology had as an approach the qualitative research, being carried out a bibliographical and field research comprising 3 municipal schools of the teaching network of the municipality of Parintins. Data were collected through a questionnaire, which was sent to 3 managers, 6 teachers from the respective investigated schools and the coordinator of Indigenous School Education. The results show that indigenous students face several integration and socialization challenges within the urban school context from an intercultural perspective; the difficulty of speaking Portuguese causes problems in interaction with the teacher and classmates; despite the limited resources, management and teaching staff are committed to working on interculturality with indigenous children; it was found that the lack of projects and educational actions generate negative impacts with regard to the contexts of coexistence, teaching and learning, building social relationships and the partnership between school and family.